Etiologies and characteristics of children with chief complaint of short stature - Kyung Chul Song; Song Lee Jin; Ah Reum Kwon; Hyun Wook Chae; Jung Min Ahn; Duk Hee Kim; Ho-Seong Kim (Annals of Pediatric Endocrinology & Metabolism, 2015)
PurposeShort stature is a very common reason for visits to pediatric endocrine clinics. It could be the first sign of an underlying disease. The purpose of this study is to investigate the etiologies and general characteristics of subjects who visited an outpatient clinic due to short stature.MethodsWe retrospectively reviewed the medical records of 3,371 patients who visited Severance Children's Hospital with the chief complaint of short stature from 2010 to 2012. Medical history, auxological data, and laboratory tests including bone age were collected and analyzed. Chromosome studies or combined pituitary function tests were performed if needed.ResultsApproximately 89.4% of the subjects with the chief complaint of short stature who visited the outpatient clinic were of normal height, and only 10.6% of subjects were identified as having short stature. Of the subject of short stature, 44.7% were classified as having normal variant short stature; that is, familial short stature (23.0%), constitutional delay in growth (17.7%), and mixed form (3.9%). Pathological short stature was found in 193 subjects (54.2%). Among pathological short stature, most common etiology was growth hormone deficiency (GHD) (38.9%).ConclusionA majority of children had a normal height. Among children with short stature, pathological short stature and normal variants occupied a similar percentage. GHD was the most common cause of pathological short stature and found in about 20% of the children with short stature. In pathological short stature, the height, height velocity, and IGF-1 level were lower than in normal variants.